Technology-Based E-Learning Innovation at MAN Kisaran - Dewi, Yuliana; Siregar, Rahmayani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze how e-learning is implemented as a technology-based educational innovation at MAN Kisaran. The research uses descriptive research methods with a qualitative approach located at MAN Kisaran. Primary data sources were obtained from several interviews with related informants, while secondary data were obtained from documents related to the research topic. Data collection techniques included observation, interviews, and documentation, with the researcher as the main instrument supported by tools such as interview guidelines and other aids. The results of this study reveal two key components of e-learning-based learning innovation: (1) Characteristics and (2) Principles. The characteristics of e-learning-based learning innovation consist of four elements: (1) Interactivity, (2) Independency, (3) Accessibility, and (4) Enrichment, all of which have been implemented effectively. Meanwhile, the principles of e-learning-based learning innovation include (1) Interaction, (2) Usability, and (3) Relevance, which have also been applied well. Additionally, there are supporting factors, such as accessibility to the e-learning website, e-learning training, and adequate human resources, as well as inhibiting factors, such as infrastructure limitations involving servers and internet networks.